WEB-BASED CAR RENTAL INFORMATION SYSTEM (CASE STUDY: CV. RAFAEL TRANS) - Oktaviani, Ayu; Sari, Yunita Sartika (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2025)
Rafael trans rental information system is an information system to support car rental activities for customers in the city and outside the city. Ttrans rafael rental still uses bookkeeping which causes frequent errors in the processing. this system was built, with the aim of being able to help manage rental data, which includes rental transaction data, payment data, car data and generate reports and provide vehicle data information to customers easily and quickly.The method used is structured and descriptive approach with a case study approach on rental rafael trans, while the software in making this system is php, mysql database, browser and xampp. From the results of the application test, it can be seen that the rafael trans rental information system application can provide convenience for customers in the car ordering process and for admin can provide convenience in managing the process of recording car bookings and rental reports.